Herpes Simplex Virus Decreases Endothelial Cell Plasminogen Activator Inhibitor - Bok, Robert A; Jacob, Harry S; Balla, Jozsef; Juckett, Margaret; Stelle, Theresa; Shatos, Marie A; Vercellotti, Gregory M (Thrombosis and Haemostasis, 1993)
Herpes simplex virus (HSV) infection is histopathologically associated with vascular injury, fibrinoid necrosis and inflammatory cell infiltrates. We have previously shown in vitro that HSV infection of human umbilical vein endothelial cells (HUVEC) promotes a procoagulant phenotype manifest by the induction of tissue factor, the loss of thrombomodulin, and an increase in platelet adhesion. In these studies we examined the effects of HSV infection on HUVEC plasminogen activator inhibitor type 1 (PAI-1) and tissue plasminogen activator (t-PA). HSV infection caused the loss of PAI-1 in the extracellular matrix (ECM) and that released into the supernatant of HUVEC. Both activity and antigen levels of the Serpin inhibitor are diminished as a result of HSV infection. The loss of inhibitor is not secondary to diminished vitronectin (Vn), the primary binding protein of PAI-1 in the ECM, but appears to be secondary to decreased synthesis at the RNA level. Tissue plasminogen activator (t-PA). synthesis is also decreased in endothelial HSV infection. PAI-1 loss may further promote a procoagulant phenotype in HSV infection in vivo.